Regulation of Reactive Oxygen Species Promotes Growth and Carotenoid Production Under Autotrophic Conditions in Rhodobacter sphaeroides - Lee, Yu Rim; Lee, Won-Heong; Lee, Soo Youn; Lee, Jiye; Kim, Min-Sik; Moon, Myounghoon; Park, Gwon Woo; Kim, Hui Su; Kim, Jeong-Il; Lee, Jin-Suk; Lee, Sangmin (Frontiers in Microbiology, 2022)
Industrial demand for capture and utilization using microorganisms to reduce CO2, a major cause of global warming, is significantly increasing. Rhodobacter sphaeroides is a suitable strain for the process of converting CO2 into high-value materials because it can accept CO2 and has various metabolic pathways. However, it has been mainly studied for heterotrophic growth that uses sugars and organic acids as carbon sources, not autotrophic growth. Here, we report that the regulation of reactive oxygen species is critical for growth when using CO2 as a sole carbon source in R. sphaeroides. In general, the growth rate is much slower under autotrophic conditions compared to heterotrophic conditions. To improve this, we performed random mutagenesis using N-methyl-N´-nitro-N-nitrosoguanidine (NTG). As a result, we selected the YR-1 strain with a maximum specific growth rate (µ) 1.44 day-1 in the early growth phase, which has a 110% faster growth rate compared to the wild-type. Based on the transcriptome analysis, it was confirmed that the growth was more sensitive to reactive oxygen species under autotrophic conditions. In the YR-1 mutant, the endogenous contents of H2O2 levels and oxidative damage were reduced by 33.3% and 42.7% in the cells, respectively. Furthermore, we measured that concentrations of carotenoids, which are important antioxidants. The total carotenoid is produced 9.63 g/L in the YR-1 mutant, suggesting that the production is 1.7-fold higher than wild-type. Taken together, our observations indicate that controlling ROS promotes cell growth and carotenoid production under autotrophic conditions.